"A Gallant Fight": The UAW and the 1970 General Motors Strike. (April 2023) - Minchin, Timothy J.
Abstract: On 15 September 1970, over 400, 000 workers struck General Motors (GM), the biggest corporation in the world. It was a massive walkout, lasting sixty-seven days and affecting 145 GM plants in the US and Canada. GM lost more than 1 billion in profits, and the impact on the US economy was considerable. Despite the strike's size, it has been understudied. Fifty years later, this article provides a re-assessment of this landmark dispute, the first to use detailed archival records of the strike. Refuting claims that the strike lacked drama, I argue that this was a multifaceted – and compelling – story. Primary sources show that workers and union leaders were heavily invested in the battle, which reflected deep-seated local, national, and global issues. The United Automobile Workers (UAW) mobilized significant levels of national and international support, and won a range of concessions, including substantial wage and benefit increases and the ability for workers to retire after thirty years' service. The strike was deeply infused by local issues and should not just be viewed through the lens of the national GM–UAW relationship. In a broader context, the strike is also important because it occurred at a time of rising global labour militancy, which scholars are increasingly recognizing. Its story contributes to a growing body of literature on the 1970s, a decade that witnessed important activism in many areas.